Thermo-responsive fluorinated surfactant for on-demand demulsification of microfluidic droplets. Issue 18 (2nd September 2021) - An, Chuanfeng; Zhang, Yujie; Li, Hanting; Zhang, Haoyue; Zhang, Yonghao; Wang, Jiamian; Zhang, Yang; Cheng, Fang; Sun, Kai; Wang, Huanan
Abstract : Thermo-responsive fluorinated surfactant can lead to destabilization of droplets and subsequently cause droplet coalescence. Thus, the encapsulated cargoes can be retrieved on-demand from the droplets without complicated processing. Abstract : Droplet microfluidics has recently emerged as a powerful platform for a variety of biomedical applications including microreactors, bioactive compound encapsulation, and single cell culture and analysis; all these applications require long-term droplet stability, which, however, makes breaking the emulsion and retrieving the loaded samples difficult. Herein, we developed a novel class of thermo-responsive fluorosurfactants to control the droplet status simply by temperature. The surfactants were synthesized by coupling perfluorinated polyethers (PFPEs) with a thermo-responsive block of poly( N -isopropylacrylamide) (pNIPAM) or poly(2-ethyl-2-oxazoline) (pEtOx) with lower critical solution temperature (LCST). These diblock surfactants can stabilize the emulsion at temperatures below LCST due to the hydrophilic head, which became hydrophobic upon increasing the ambient temperature above LCST, thereby destabilizing the droplets and realizing demulsification simply via temperature control. The diblock surfactant can be applied for templating cell encapsulation using alginate microgels, which allowed one-step and high-throughput microfluidic generation of cell-laden microgels without compromising cell viability. This non-invasive, on-demand demulsification strategy provides a high degree of freedom for microencapsulation and on-demand recovery of the samples or reaction products within the droplets, which opens a new avenue for a wide range of applications of droplet-templating microfluidics.